Aleurites moluccanus and its main active constituent, the flavonoid 2″-O-rhamnosylswertisin, in experimental model of rheumatoid arthritis. (10th May 2019) - Quintão, Nara Lins Meira; Pastor, Maria Verônica Dávila; Antonialli, Carla de-Souza; da Silva, Gislaine Francieli; Rocha, Lilian Wünsch; Berté, Talita Elisa; de Souza, Márcia Maria; Meyre-Silva, Christiane; Lucinda-Silva, Ruth Meri; Bresolin, Tania Mari Belle; Cechinel Filho, Valdir
Abstract: Ethnopharmmacological relevance: Aleurites moluccana is used in folk medicine to treat pain, fever, asthma, hepatitis, gastric ulcer and inflammatory process in general, and the nut oil had been topically applied to treat arthritis and other joint pain, however the seeds are classified as toxic for oral use. Aim: Faced with the need for new alternative to treat the symptoms and modify rheumatoid arthritis (RA) the aim of this work was to evaluate the effects of A. moluccanus' leaves dried extract in rats and mice submitted to complete Freund adjuvant (CFA)-induced RA. Material and methods: Wistar Rats and Swiss mice were submitted to CFA-induced RA in the right hindpaw. They received A. moluccanus extract (orally; p.o.), dexamethasone (subcutaneously), 2″- O -rhamnosylswertisin (p.o.) or vehicle (p.o.), from the 14th day after the CFA injection for up to 8 days. The mechanical hypersensitivity was evaluated using the von Frey filaments and the paw-oedema was measured using a plethysmometer. The rats' injected hindpaw was used to perform the histological analysis. Results: A. moluccanus was able to significantly reduce the mechanical hypersensitivity in both ipsi- and contralateral hindpaws of mice injected with CFA, in a dose dependent manner. Furthermore, the paw-oedema was progressively reduced by A. moluccanus . Similar results were obtained for the positive-control drug dexamethasone and the isolated compound 2″- O -rhamnosylswertisin. Besides the effects mentioned above, the extract was also effective to repair the joint damage in CFA-induced RA rats, including reduction of fibrosis, cartilage degradation and bone erosion scores. Conclusion: These results together with the literature data reinforce the anti-hypersensitivity and anti-inflammatory activity of A. moluccanus extract. Part of the observed effects is due to the presence of the compound 2″- O -rhamnosylswertisin. The fact that the extract acted as a disease modifier point this herbal product as a promisor and safe tool to treat RA and other associated chronic diseases. Graphical abstract: fx1